Donkey-assisted rehabilitation program for children: a pilot study - Paola De Rose; Elisabetta Cannas; Patrizia Reinger Cantiello (Istituto Superiore di Sanità, 2011)
Bonding with animals grants access to the sphere of affectivity and facilitates therapeutic engagement. The methodological approach of donkey-assisted programs is based on mediation, which is characterized by multidirectional relationships (patient-donkey-therapist). The donkey is an excellent facilitator in the motivation-building process, being able to stimulate the child's development by way of active and positive forces that foster psycho-affective and psycho-cognitive development processes. Results of this study, which focused on the child's approach to the donkey, indicate that while communicating with the animal, children rely more on physical expressions than on verbal language. Donkey-assisted rehabilitative sessions can help in identifying children's strong points, on which motivation could be built.